Preferensi Investor terhadap Strategi Investasi di Pasar Modal - Muhammad Fachruddin A. Adhikara (The Indonesian Journal of Accounting Research, 2013)
This research responses issues about securities investment in capital market impacted by the process of mental discounting and its various preferences among investor in making the accurate type strategy of securities investments.The investor had preference of utility on income subjective discounted interest rate in speculative, aggressive, core type investment strategy and foundation capital. Using domain on investment strategy, the researcher  hypothesized that discounted interest rate of subjective preference to escort domain investment strategy had different level mean, variance, and model. Analyses were based on 303 investors in 4 clusters (speculative strategy, aggressive strategy, core strategy, and foundation capital strategy) of members of Masyarakat Investor Sekuritas Indonesia (MISI).The result shows that discounted interest rate between domain investment strategy has mean level and explained model differently, but has not different variance as told that subjective discounted interest rate preferences  equal to the risk of investors preference. This  indicates that maximum utility investor on income suggested to get optimal return with the same risk. Related to the impact of turbulence market factor on bearish condition, investors have no risk preference. This result also show speculative, aggressive strategy, core strategy model of domain investment, and foundation capital strategy are different among group.